Implementasi Kurikulum Merdeka untuk Meningkatkan Perkembangan Holistik Siswa dalam Pembelajaran Pendidikan Agama Islam (PAI) di MTs MINAT Kesugihan Cilacap - Ali Abdurroziq; Muh. Hanif (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
In the context of post-pandemic learning recovery, the Ministry of Education and Culture has officially implemented the latest curriculum entitled independent learning which will begin to be implemented in the 2022/2023 academic year in all educational units independently. The aim of this research is to describe the implementation of the independent curriculum in Islamic Religious Education learning at MTs MINAT Kesugihan as well as the positive impacts and obstacles in implementing the independent curriculum in Islamic Religious Education learning at MTs MINAT Kesugihan. This research applies a qualitative phenomenological approach to the field study type. Data collection techniques were carried out through observation, interviews and document study. The research results show that the independent curriculum implementation process is broken down into three stages, namely planning, implementation and evaluation. The positive impacts of implementing the independent curriculum on Islamic Religious Education learning include increasing teacher and student creativity, increasing student enthusiasm and activeness in learning, and increasing teacher enthusiasm in developing their own capacity. The obstacle in implementing the independent curriculum in Islamic Religious Education learning is the difficulty of educators in creating fun and quality learning and determining the right themes and content for P5 activities to suit students' interests and talents.